2010
DOI: 10.1007/bf03256369
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of IDH1 Mutations Identified with PCR-RFLP Assay in Glioblastoma Patients

Abstract: Our results indicate that the IDH1 R132H mutation is a powerful prognostic marker in GBM treated with chemoradiation. The PCR-RFLP method allows for a fast, inexpensive, and sensitive mutation screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Bujko et al 60 and Meyer et al 61 have adapted PCR-based restriction fragment length polymorphism assays to detect mutations in codon 132 of the IDH1 gene. These assays, also known as derived cleaved amplified polymorphic sequence analysis, are based on the presence or absence of a restriction enzyme binding site at codon R132 in IDH1 , depending on the presence or absence of mutation.…”
Section: Detection Of Idh Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bujko et al 60 and Meyer et al 61 have adapted PCR-based restriction fragment length polymorphism assays to detect mutations in codon 132 of the IDH1 gene. These assays, also known as derived cleaved amplified polymorphic sequence analysis, are based on the presence or absence of a restriction enzyme binding site at codon R132 in IDH1 , depending on the presence or absence of mutation.…”
Section: Detection Of Idh Mutationsmentioning
confidence: 99%
“…Identifying the specific IDH1 mutation present requires additional assays using multiple PCR primer pairs and restriction enzymes and is therefore quite labour intensive. However, the tests are relatively rapid and have the advantage of not requiring expensive sequencing equipment 60 61. We have found this technique useful for screening purposes (mutant vs wild type in antibody-negative cases; figure 2B,C), and for the confirmation of equivocal sequencing results.…”
Section: Detection Of Idh Mutationsmentioning
confidence: 99%
“…A number of methods have been developed to detect IDH1 mutations including DNA sequencing (4,17), PCR-restriction fragment length polymorphism (RFLP) (18,19), PCR-single strand conformation polymorphism (SSCP) (20), pyrosequencing (21,22), and high-resolution melting curve analysis (HRM) (23,24). All of these methods have limitations in terms of sensitivity, ease of use and throughput.…”
Section: Comparison Of Immunohistochemistry Dna Sequencing and Allelmentioning
confidence: 99%
“…Various studies have identified candidate prognosis factors for GBM (Bujko et al, 2010; Burger and Green, 1987; Davis et al, 1949; Ohgaki et al, 2004; Stupp et al, 2005), yet it has remained unclear how best to account for the joint effects of multiple factors. In an attempt to address this problem, researchers have proposed multivariate prognosis models (Colman et al, 2010; Lamborn et al, 2004; Liang et al, 2005; Nutt et al, 2003), which attempt to account for multiple effects simultaneously.…”
Section: Introductionmentioning
confidence: 99%